Digital financing for SMEs' recovery in the post-COVID era: A bibliometric review - Pellegrino, Alfonso; Abe, Masato (Frontiers in Sustainable Cities, 2022)
The restrictions that have been implemented due to the COVID-19 pandemic have highlighted the growing importance of digital financing. While traditional banking services have been restricted by social distancing, limited work hours, and lockdowns, digital financial services can deal effectively with those restriction measures while facilitating governments to channel relief and stimulus funds to small and medium-sized enterprises (SMEs). However, adequate and proper regulations and protections are required to deal with issues such as cybersecurity, which could limit the favourability of digital financial services with increasing risks to stability and integrity. This paper analyzes, by using the bibliometric review approach along with the VOSviewer, a bibliometric mapping software, 629 Scopus journal articles relevant to the key components of digital financing for SMEs under the pandemic. Based on the review, it identifies the most crucial policy areas for digital financing. The paper presents policy implications on how digital financial services can support SMEs in dealing with COVID’s challenges.